Climate-smart harvesting and storing of water: The legacy of dhaka pits at Great Zimbabwe. (December 2022) - Pikirayi, Innocent; Sulas, Federica; Nxumalo, Bongumenzi; Sagiya, Munyaradzi Elton; Stott, David; Kristiansen, Søren M.; Chirikure, Shadreck; Musindo, Tendai
Abstract: Understanding past water management is crucial to address contemporary human-environmental challenges in sub-Saharan Africa, where urban growth is impacting upon water availability and supply. This study integrates soil profiles, high-resolution topographic data, historical sources, and socioecological memory to reconstruct how the ancient urban society at Great Zimbabwe negotiated water security. New evidence shows for the first time that closed depressions known as dhaka pits were used by the inhabitants of Great Zimbabwe for water storage and harvesting for a long time, possibly since the emergence of settlement in the mid-second millennium CE. These pits were part of a landscape-scale water management system that exploited catchment hydrology and groundwater by means of artificial dhaka reservoirs, wells, and springs to secure water for subsistence, farming, ritual and ceremony services. This study highlights the need for precise dating of the construction and functioning period of this water management system at Great Zimbabwe. Understanding past water management in such a water-scarce region is important for reconstructing how the ancient Great Zimbabwe urban society negotiated water security, but also for understanding contemporary human-environmental challenges. Highlights: Remote sensing and geoarchaeology reveal past water use at Great Zimbabwe (83). Large dhaka pits fed an integrated water management system at Great Zimbabwe (80). There is continued use of springs and wells to mitigate water shortages (74). Urban centres in Zimbabwe today can draw lessons from Great Zimbabwe (68).